Bioethics and right (s): some perspectives - Kottow Lang, Miguel (2016)
Interrelations between bioethics and human rights have been debated ever since this applied ethics has developed over the last 50 years. Persistent controversies regarding the Universal Declaration of Human Rights, the disciplinary status of bioethics, and their interaction as presented by the Universal Declaration on Bioethics and Human Rights, all require renewed reflection. Theoretical debates have had to face the reality of global social issues with their tendency to maintain, even naturalize, social, regional and transnational inequalities, in the weakened moral climate of late modernity’s individualism, the dominance of neoliberalism, and reduced social protection that neglects the common weal. The present article reinforces the need for reflexive bioethical discourse as a crucial element in social practices that tend to be legalized.